Determinants of Arrears in Payment of Health Social Security Organizing Bodies for Independent Participants - Fikri Khairusshidqi Rizqullah; Dwi Noerjoedianto; Adila Solida (Jurnal EduHealth, 2023)
The Social Security Administrative Body (BPJS) for Health is a legal entity established to administer a health insurance program with objective every inhabitant country get chance And equal rights in obtaining health services. However , based on data obtained from BPJS Health, it is recorded that there are 5 districts in Jambi Province that are in arrears in paying BPJS contributions . One of them is Jambi City happen arrears with the most dues of 76,909,256,816. According to the BPJS Health program rules, payment is requested no later than the 10th of each month. Hence the goal _ in study This is find out the determinants of arrears in payment of Health Social Security Administering Body contributions for independent participants in the city of Jambi.This study used a quantitative method with a cross-sectional research design. The sample in this study were 106 respondents using a purposive proportional random sampling technique. Data collection used a questionnaire and data analysis used univariate and bivariate (chi-square). The results of this study indicate that the majority of 61.3% of respondents are in arrears and based on statistical tests in this study indicate that there are factors related to arrears in BPJS contribution payments, namely income (0.000), knowledge (0.013), perception (0.011), and place of payment (0.002). There is a relationship between the variables where contributions are paid, income, knowledge and perceptions with BPJS contribution arrears.